Volume Stability of Bitumen Bound Building Blocks - Thanaya I.N.A. (Institute of Research and Community Outreach - Petra Christian University, 2010)
This paper covers results of laboratory investigations on the volume stability of masonry units incorporating waste materials bound with bitumen (Bitublocks), due to moisture adsorption, thermal exposure and vacuum saturation. The materials used were steel slag, crushed glass, coal fly ash, and 50 pen bitumen. The samples were produced in hot mix method, compacted, then exposed to moist and temperature. It was found that moisture adsorption from the environment caused the Bitublock to expand. The samples with less intense curing regime experienced lower expansion and became stable faster, and vice versa. Under thermal condition (at 70°C), the samples with less intense curing regime underwent higher expansion, and vice versa. They were also highly reversible. Their volume stability was found unique under water exposure. The expansion on first vacuum saturation cycle was irreversible, then largely reversible on the following cycles.